Capillary blood flow in the canine colon and other organs at normal and raised portal pressure. Issue 3 (March 1981) - Grandison, A S; Yates, J; Shields, R
Abstract : Capillary blood flow in the canine colon and other organs has been assessed over a wide range of portal pressures using radio-labelled microspheres. The proximal colon received a greater proportionate flow than the distal region. At both normal and raised pressures, the mucosa received 90% of the total colonic capillary flow. A highly significant negative correlation (P less than 0.001) was found between colonic capillary blood flow and portal pressure. A highly significant positive correlation (P less than 0.001) was found between colonic capillary blood flow in the superior mesenteric artery.